2019
DOI: 10.3233/jad-190220
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG Is a Superior Indicator of Cognitive Performance Compared to 18F-Florbetapir in Alzheimer’s Disease and Mild Cognitive Impairment Evaluation: A Global Quantitative Analysis

Abstract: Background: 18 F-Fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET) and 18 F-florbetapir PET are approved neuroimaging biomarkers for the Alzheimer's disease (AD) and mild cognitive impairment (MCI).Objectives: This study aims to compare the efficacy of 18 F-FDG and 18 F-florbetapir PET at evaluating the cognitive performance of patients with AD, MCI, and normal controls (NC). Methods: 63 subjects (36 male/27 female, mean age = 68.3) including 19 AD, 23 MCI, and 21 NC underwent 18 F-FDG and 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Data from the approach have similarly demonstrated great importance in patients with cancer, atherosclerosis, systemic inflammation, and musculoskeletal disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig. 2 Maximum intensity projection (MIP) FDG PET/CT scans of a 60-year-old patient with multiple myeloma ( A ) pretreatment 1 hour and ( B ) pretreatment 3 hours after administration of FDG.
…”
Section: Practical Clinical Applicationsmentioning
confidence: 99%
“…Data from the approach have similarly demonstrated great importance in patients with cancer, atherosclerosis, systemic inflammation, and musculoskeletal disorders. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig. 2 Maximum intensity projection (MIP) FDG PET/CT scans of a 60-year-old patient with multiple myeloma ( A ) pretreatment 1 hour and ( B ) pretreatment 3 hours after administration of FDG.
…”
Section: Practical Clinical Applicationsmentioning
confidence: 99%
“…This partly relates to the structural location of uptake of the agents that target these plaques and partly to their non-specific concentration in the adjacent tissues including the white matter. As such, a recent publication comparing results of FDG-PET imaging to those of amyloid scan data, further confirmed the superior performance of FDG-PET and the limitations of "amyloid imaging" in the evaluation of patients with mild cognitive impairment (MCI) and AD [33].…”
Section: The Introduction Of 2-deoxy-2-[f-18]fluoro-d-glucose (Fdg) (mentioning
confidence: 73%
“…In familial AD, the cascade of Abeta, then altered metabolism and then atrophy is definitive [ 24 ]. Khosravi et al's study revealed FDG global quantification to be a superior indicator of cognitive performance in the AD and MCI patients compared to 18F-florbetapir-PET [ 25 ]. However, recent research has indicated that increased Abeta deposition leads to the progression to mild cognitive impairment but decreased glucose metabolism does not contribute to progression [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%